Fourier Expression of the Quantum Radar Cross Section of a Dihedral Corner Reflector - Zhifu Tian; Di Wu; Tao Hu (IEEE Photonics Journal, 2021)
In this paper, a Fourier expression of the quantum radar cross section (QRCS) of a dihedral corner reflector is proposed, which avoids the problems caused by atomic sampling on the target-object surface and is a powerful tool for analyzing the scattering characteristics of the reflector. We compare the result of the proposed expression with that of numerical calculations, and have preliminarily verified its correctness. On this basis, we discuss the influence of the wavelength of single photon pulses and the panel size of a dihedral corner reflector on QRCS in detail. Simulation results demonstrate that from a single factor of wavelength, a quantum radar using a small-wavelength quantum signal has better visibility to the reflector, and the quantum scattering intensity is proportional to the panel size. Compared with classical radar, quantum radar has an enhanced detection performance that is more stable within a wide angle range, which is insensitive to the wavelength of the quantum signal and panel size of the reflector and is helpful for the detection of stealth targets.